Increasing The Appreciation Of Fine Art Through Participatory Murals At Perum Arjamukti Singaparna, Tasikmalaya Regency - Wan Ridwan Husen; Asep Wasta; Denden Setiaji; Arni Apriani; Agi Fajri Nur; Helda Safaat; Mega Utami; Widya Imardhea; Alfi Munajab (AbdimasMu UMTAS, 2022)
This paper aims to provide an overview of activities that seek to bring the process of art education directly to the public Community service that started from a discussion between lecturers and youth youth organizations at Perum Arjamukti Kencana in building a tourist village area around Singaparna, Tasikmalaya Regency, from this discussion arose a desire to create activities that involve residents and youth youth groups in arts-related activities. A participatory mural is a mural activity that involves the participation of citizens in its implementation, both before implementation, in its manufacture and after its creation. The method used in this research is descriptive method. The descriptive method used to increase the appreciation of fine arts through participatory murals at Perum Arjamukti Singaparna, Tasikmalaya Regency. The results obtained from research that have been carried out by residents' wishes in the mural participation process are varied, the forms of citizen participation are not only in the form of trying to scratch koas on walls to produce mural images, there are also those who participate in providing consumption, raw materials, documenting works through social media or simply just talking and taking selfies on existing murals.